Pesantren Responses to Religious Tolerance, Pluralism and Democracy in Indonesia - Nurrohman Nurrohman (International Journal of Nusantara Islam, 2014)
Pesantren (Islamic boarding school) is the oldest Islamic institution in Indonesia that often affiliated to the largest mass Muslim organization Nahdlatul Ulama. This organization is well known for its stance to uphold moderate, tolerance Islam and accepting pluralistic state based on Pancasila. Pesantren also often referred as the barometer to understand the way of thinking of Muslims grass root in Indonesia because many Islamic figures in Indonesian village are alumni of pesantren.  There are debates among scholars on whether religious violence has a root in religious doctrine or it is caused by factors outside religion such as poverty or injustice. By assuming that both inside and outside factors have significant contribution to violence or radicalism this study will discuss the doctrine that potentially can be used to justify violence and intolerance by reviewing the opinion of pesantren leaders in West Java on jihad, violence or intolerance and power. This study is aimed to examine whether the commitment of Muslim leaders in national level on democracy and plurality is supported by grass root particularly from pesantren leaders.  Overall the study found that although they agree that democracy is compatible with Islam, this study reveals that their acceptance to pluralism still be questioned as evidenced by almost half of them supported theocratic caliphate carry out by radical group. Although many argued that pesantren promotes tolerance and pluralism, nevertheless this  study shows that some of their teaching tacitly supported violence act in the name of religion that will tarnished the effort of Indonesia to synchronize Islam, democracy and modernity. It means that many of them actually not wholeheartedly accepted democracy and pluralism.